PENGARUH TATA KELOLA PERUSAHAAN TERHADAP EFFECTIVE TAX RATE PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI 2019-2021 - Odila Levana Ng; Temy Setiawan (Jurnal Bina Akuntansi, 2023)
This study aims to determine the effect of corporate governance on the Effective Tax Rate (ETR) with the independent variable good corporate governance explained by independent compensation, executive character, company size, institutional ownership, independent commissioners, audit committee and audit quality and the dependent variable, namely the effective tax rate. The method used in this research is descriptive quantitative method. The research sample uses the annual reports of 93 manufacturing companies on the IDX for 2019-2021 with a total of 240 datas after the occurrence of outliers. The analytical method uses multiple linear regression models using the Statistical Package for the Social Science (SPSS) version 25. The results of this study indicate that the variable company size, audit committee and audit quality have a significant effect on the Effective Tax Rate. Meanwhile, the variables of executive compensation, executive character, institutional ownership, and independent commissioners have no effect on the effective tax rate.